Seismic and Microseismic Signatures of Fluids in Rocks: Bridging the Scale Gap. Issue 6 (23rd June 2019) - Sarout, J.; David, C.; Pimienta, L.
Abstract: The aim of this collection is to record a snapshot of our current state of understanding of the impact of fluids on the evolution and monitorability of subsurface rock formations during anthropogenic fluid injection/withdrawal operations, accounting for scale and frequency effects. In this introduction we provide a summary of the key challenges and findings reported in these 23 articles. This suite of articles addresses a variety of issues related to the impact of fluids on subsurface rocks, which can be grouped in three themes: (i) impact of fluids on wave velocity and attenuation/dispersion (five articles); (ii) fluids, fractures, and seismicity (nine articles); and (iii) dynamic fluid injection and substitution (nine articles). Key Points: Impact of fluids on wave velocity and attenuation/dispersion Fluids, fractures, and seismicity Dynamic fluid injection and substitution